2010
DOI: 10.1111/j.1365-246x.2010.04598.x
|View full text |Cite
|
Sign up to set email alerts
|

Error distribution in regional inversion of potential field data

Abstract: S U M M A R YAn increasing number of regional inversions of gravity and magnetic field data have recently been computed, some based on satellite and ground data, some on satellite data only. In each case it is important to quantify the errors resulting from the confined data region or the satellite parameters. In this study we investigate the error distribution of regional inversions for scalar gravity and vector geomagnetic data from satellite data only. We include the effects of satellite altitude, size of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Indeed, it arises whenever different data sets and/or models with various spatial or temporal resolutions are to be merged for interpretation e.g. in seismology and geomagnetic studies (Trampert and Snieder 1996;Boschi and Dziewonski 1999;Schachtschneider et al 2010;Schott and Thébault 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it arises whenever different data sets and/or models with various spatial or temporal resolutions are to be merged for interpretation e.g. in seismology and geomagnetic studies (Trampert and Snieder 1996;Boschi and Dziewonski 1999;Schachtschneider et al 2010;Schott and Thébault 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found empirically that an extension of 5 • reduces the distortions over the area of interest to a level below 2 mm. This result is independent of the size of the area of interest as shown in (Schachtschneider et al 2010). Hence, only for data areas much smaller than the one considered in the numerical experiments of Sect.…”
Section: Impact Of the Size Of The Data Areamentioning
confidence: 84%
“…These distortions, which are usually referred to as edge effects, reduce towards the centre of the data area (e.g. Schachtschneider et al 2010). Hence, to reduce the distortions, the data area has to be chosen larger than the area of interest.…”
Section: Impact Of the Size Of The Data Areamentioning
confidence: 99%
“…The error distributions obtained in case of elliptical data regions look very similar to the ones obtained in circular data region experiments ( cf. Schachtschneider et al 2010). The minimum value is reached in the centre, the error increases towards the boundary where the maximum is reached.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases there are edge effects that have to be taken into account. The boundary region that is necessary and a comprehensive error analysis for circular spherical cap shaped regions is found in Schachtschneider et al (2010).…”
Section: Introductionmentioning
confidence: 99%